2015
DOI: 10.3109/00016489.2014.968673
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary therapeutic management of locally advanced hypopharyngeal cancer: oncologic and functional outcomes – a report on 100 cases

Abstract: A total of 100 patients were included in this study. Induction chemotherapy (CT) followed by radiotherapy (RT) ± CT, primary RT + CT, and primary total pharyngolaryngectomy (TPL) comprised the initial therapeutic management for 54, 24, and 20 patients, respectively. Two patients received only supportive care. Overall survival (OS) and cause-specific survival (SS) were 50% and 60% at 3 years, respectively. In the group of patients referred for induction CT, the 3-year OS and SS were 58% and 70%, respectively. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The systematic review included 2 randomised controlled trials 11 , 33 and 11 observational studies 9 , 26 , 27 , 34 41 . A thorough search of PubMed and Medline, Embase, Scopus, the Cochrane Library, and Google Scholar yielded 5639 citations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The systematic review included 2 randomised controlled trials 11 , 33 and 11 observational studies 9 , 26 , 27 , 34 41 . A thorough search of PubMed and Medline, Embase, Scopus, the Cochrane Library, and Google Scholar yielded 5639 citations.…”
Section: Resultsmentioning
confidence: 99%
“…All 11 non-randomised studies were retrospective observational studies that were published in English 9 , 26 , 27 , 34 41 . All studies with the exception of two reported data only on advanced stage hypopharyngeal cancer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypopharyngeal carcinoma has one of the poorest prognoses of all head and neck carcinomas as it is frequently diagnosed at an advanced stage and exhibits aggressive and distant metastasis ( 1 ). Although there have been significant advancements in surgical techniques and chemoradiotherapy recently, the prognosis of hypopharyngeal carcinoma remains unsatisfactory ( 2 ).…”
Section: Introductionmentioning
confidence: 99%